THE ROLE AND IMPORTANCE OF TOURISM INFRASTRUCTURE IN THE DEVELOPMENT OF REGIONAL TOURISM - Mirza Qilichbayevich Sabirov (Antis Publisher, 2024)
This article focuses on the challenges of developing regional tourism infrastructure. The article also defines the essence of the concept of